Pendidikan Sebaya Meningkatkan Pengetahuan Remaja Awal tentang Kesehatan Reproduksi (Studi Pada Sekolah Menengah Pertama di Kabupaten Subang, Jawa Barat) - Juariah Juariah (Kesmas Indonesia, 2021)
Teenagers face various reproductive health problems including sexuality, sexually transmitted diseases and HIV / AIDS as well as smoking and drug abuse. Peer involvement as an educator that begins in the school environment can be an effort to share information and discuss reproductive health issues. This study aimed to analyze the effect of peer education on early adolescents knowledge about reproductive health. The study used a pre-experimental design method with pretest and posttest one group design, that conducted at Junior High School 1 and 2 Pusakajaya Subang Regency West Java, on July to November 2018. The sample was determined purposively. Data were collected by questionnaire as a form of pretest and posttest and analyzed by paired sample t-test. Respondents who participated in all stages of the study were 254. They were 125 boys and 129 girls. The results showed that there was a difference in the average of pretest and posttest scores for boys (4,48) and girls (6,8) participants. Results of bivariate analysis showed the p_value < 0.05. This means that peer education provided a significant influence on increasing participants' knowledge about adolescent reproductive health. Therefore, peer education should be applied continuity and be developed both in schools and outside of schools.